Excitation of internal m = 1 mode during application of resonant magnetic perturbations on J-TEXT tokamak. (8th June 2017) - Li, Jianchao; Hu, Qiming; Ding, Yonghua; Zhang, Xiaoqing; Yu, Qingquan; Yang, Zhoujun; Chen, Zhipeng; Li, Da; Rao, Bo; Wang, Nengchao; Zhuang, Ge
Abstract: The excitation of internal m = 1 mode during application of resonant magnetic perturbations (RMPs) is observed on J-TEXT tokamak. It is found that the sawtooth oscillation disappears after RMPs penetration, and subsequently an internal m = 1 mode with a frequency around 2 kHz appears, were m and n are the poloidal and toroidal mode numbers, respectively. In addition, the internal m = 1 mode often coexists with a rotating m / n = 2/1 tearing mode, and its frequency increases by about 0.5 kHz when the 2/1 tearing mode is locked by RMPs. The bispectrum analysis proves that the m = 1 mode interacts with the rotating 2/1 tearing mode, which implies the mode coupling between these two modes. The frequency of m = 1 mode increases for higher electron density. These results reveal that, the internal m = 1 mode can be excited by RMPs and coexist with both locked and rotating 2/1 mode due to toroidal mode coupling.